(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
Waqf is a form of charity which ishighly recommendedin Islam. In Malaysia, most of the states impose solely on perpetuity property based on Shafiᶜiy school of law view as stated in State Administration of Islamic Law Enactment and State Waqf Enactment. However, there are certain states allowed the implementation of temporary waqf such as Johor, Federal Territory of Kuala Lumpur, and Sarawak. In 2020, most of the country across the world including Malaysia are affected by deadly disease which is known as COVID-19. The World Health Organization (WHO) declare it as pandemic on January 2020. Malaysia Government has issued Movement Control Order (MCO) as a preventive measures to overcome this contagious disease. Many institutions and employment sectors are ordered to stop their operation temporarily. The negativeimpact of MCO affected daily life routine, public safety and security, education, and business. Thus, the objective of this paper is to study the concept of temporary waqf from the Islamic perspectives and to explore the advantages of temporary waqf in combating COVID-19. This paper has conducted inductive and deductive methods. In this qualitative research, data has been collected by using library research, observations, and interview. The result of this paper shows that temporary waqf products brought many advantages as compared to perpetuity waqf in combating this pandemic COVID-19.